Diagnosis of Idiopathic Pulmonary Fibrosis in a Possible Usual Interstitial Pneumonia Pattern: a meta-analysis - Heekyung Kim (Nature Portfolio, 2018)
Abstract This study aimed to determine whether a surgical lung biopsy is essential for IPF diagnosis with the possible UIP CT pattern. We performed literature searches of the MEDLINE and EMBASE databases and included studies that conducted a radiologic-pathologic evaluation of IPF according to the 2011 guideline. Outcomes were pooled using a random-effects model. Twelve studies were included. Pooled proportions of IPF for a UIP pattern were 99% (95%CI, 93% to 100%; I2 = 51.7%) and for a possible UIP pattern were 94% (scenario inclusive of probable IPF; 95%CI, 87% to 99%; I2 = 82.9%) and 88% (scenario exclusive of probable IPF; 95%CI, 79% to 95%; I2 = 82.7%). The pooled percentage difference in the proportion of IPF between the UIP and possible UIP patterns was −2% (95%CI, −4% to 1%; I2 = 0.0%) in the former scenario and 4% (95%CI, 0% to 8%; I2 = 0.1%) in the latter scenario. The proportion of IPF with the possible UIP pattern was moderately correlated with the prevalence of IPF (correlation coefficient, 0.605; 95%CI, 0.550–0.860). There was a negligible pooled percentage difference in the proportion of IPF between the UIP and possible UIP patterns, indicating that IPF diagnosis can be confirmed without biopsy in suspected IPF cases with the possible UIP pattern.